Partnerships and Sustainability - Consortium Press, Appalachian (Appalachian State University, 1995)
The Sixth Biennial Linear Parks Conference was held in Blacksburg, Virginia, on September 9-11, 1995. Contributors to the proceedings are Steven Elkinton; Christopher D. Jones and William E. Hammitt; Philip A. Grant Jr.; Michael Mastrota; M. Rupert Cutler; Thomas G. Yahner, Timothy P. Johnson, Neil P. Korostoff, and A. Mark Battaglia; Terry L. Clements; Kenneth R. Tamminga; and Susan M. Smith and Stefanie Mixon.